The Effectiveness of E-Learning with the Assistance of Linktree and Whatwall on Science Learning Outcomes for Fifth Grade Students at Karangreja 01 Elementary School in Cimanggu - Sumiyati Sumiyati; Wanda Nugroho Yanuarto (Proceedings Series on Social Sciences & Humanities, 2025)
Study This aiming For measure effectiveness assisted e-learning Linktree and WhatWall to results Study students on the material properties light in class V SDN Karangreja 01 Cimanggu. The method used in study This is experiment with pretest-posttest control group design. Subjects study consists of from two groups, namely group experiments using assisted e- learning Linktree and WhatWall as well as group control that uses method learning conventional. Research result show that there is significant improvement in results Study students who use assisted e-learning Linktree and WhatWall compared to with group control. Students in group experiment more active in follow learning, discussing, and access material through Linktree and WhatWall. In addition , the response student to the use of this media is very positive, because they feel more easy understand materials and more motivated in Study. Conclusion from study This is that learning based on e-learning with help Linktree and WhatWall effective in increase results Study as well as involvement student in science learning , especially on the material properties light. Therefore that, it is recommended for teachers to utilise this digital technology in the learning process use increase effectiveness and results Study student.